Development of Human Capital Indicators to Improve Employee Performance - Rizka Apriyani Daulay; Dimas Anggi Restu; Mohammad Hamidul Haqque (Yayasan Darussalam Bengkulu, 2023)
This article provides a review of various theories, models, and methods used to measure, develop, and utilize human capital. The review evaluates and compares different approaches, theories, and methodologies used in human capital research. The authors aim to identify trends and areas of research that require further exploration. The article also discusses the difference between human capital and human resources and various methods used to measure human capital. The research methodology used in the study involved a three-way approach, including field research, literature review, and open-ended questionnaires. The article discusses the importance of developing and measuring human capital indicators for organizations to improve their effectiveness and productivity. It highlights three stages of research to identify key human capital indicators, including employee competence, job accountability, professional experience, employee commitment, teamwork, skills, creativity, professional knowledge, organizational tenure, and education level. The article also emphasizes the importance of managing and measuring human capital sustainably to improve organizational effectiveness. The study concludes that education and health play a vital role in developing human capital and contributing to regional economic growth.